The Other Animal of Transplant's Future - Sharp, Lesley A. (The Hastings Center report, 2018)
As an anthropologist, I have long been interested in highly experimental science, with my work engaging the moral underpinnings of xenoscience and, more recently, lab animal research. The possibility of employing animals as human “matches” sparks enthusiastic responses among researchers who imagine various creatures as lucrative “donor species” or “source animals” whose organs might replace the failing parts of humans and render obsolete any future need for brain-dead donors. When we attend to how xenoscientists imagine the promissory qualities of various species, we encounter a specialized logic of how and why one type of animal is valued over another. Well-established bioethical principles might assist us in framing our position in reference, say, to the limits of human suffering, or how to weigh the worth assigned to human versus animal lives, or how we conceive “the quality of life.” But sadly, subjective experience can creep in to shape and cloud those very stances we regard as bioethically principled. Rather than pursue such a well-worn path, I suggest an alternative framework that privileges attentiveness to everyday thought and action over codified bioethics. This framework—described as “everyday” or “ordinary ethics” in anthropology—involves assuming a critical, self-reflexive stance in reference to quotidian ways of seeing and knowing. Like John Berger, who famously asked, “Why Look at Animals?,” I ask, when we look at the lab-based baboon, chimp, or pig, what do we see? How do we think of, or presume to know, the animal in question? How do we think about human-animal relations in science?